ANALISIS KENAKALAN MAHASISWA DAN IMPLIKASINYA TERHADAP LAYANAN BIMBINGAN KONSELING DI STIT SYEKH MUHAMMAD NAFIS TABALONG - Nurhayati Nurhayati (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This research aims to find out about the analysis of student delinquency and its implications for guidance and counseling services at STIT Syekh Muhammad Nafis Tabalong. The research method used by the author is a qualitative method with a descriptive approach, namely by collecting data as it is from a symptom of a phenomenon that existed when the research was carried out. The data and data sources in this research are Guidance and Counseling Lecturers and students through survey techniques. The research instruments used in this research are documentation, interviews and observation. Interviews were conducted with Guidance and Counseling Lecturers and observations were made by observing the state of the university environment and the existence of the university. Data analysis techniques are carried out by collecting data, grouping data, analyzing data and interpreting data that will be concluded as research results. The conclusion of this research is that the analysis of student delinquency and its implications for guidance and counseling services at STIT Syekh Muhammad Nafis Tabalong is in the quite good category.